2013
DOI: 10.1002/wcs.1251
|View full text |Cite
|
Sign up to set email alerts
|

How thought is mapped into words

Abstract: To English speakers, the distinctions between blue and green, cup and glass, or cut and break seem self-evident. The intuition is that these words label categories that have an existence independent of language, and language merely captures the pre-existing categories. But cross-linguistic work shows that the named distinctions are not nearly as self-evident as they may feel. There is diversity in how languages divide up domains including color, number, plants and animals, drinking vessels and household contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 123 publications
(153 reference statements)
4
84
0
Order By: Relevance
“…It also is noteworthy that when words enter the architecture, they sculpt it in many fine-grained ways, for they are essentially language-particular coding devices that have been culturally designed to package concepts for communicative purposes (Malt and Majid, 2013;Tomasello, 2014). Extending the original ideas of Paivio (1986), some researchers have proposed that the statistical co-occurrence patterns of word-forms across discourses can give rise to a "disembodied" form of conceptual knowledge, and a number of computational studies have shown that, on the basis of such associations among word-forms, it is possible to model a variety of psycholinguistic phenomena, including priming effects, sentence completions, ambiguity resolution, and the extraction of gist from texts (Burgess & Lund, 1997;Landauer & Dumais, 1997;Griffiths et al, 2007;Jones & Mewhort, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It also is noteworthy that when words enter the architecture, they sculpt it in many fine-grained ways, for they are essentially language-particular coding devices that have been culturally designed to package concepts for communicative purposes (Malt and Majid, 2013;Tomasello, 2014). Extending the original ideas of Paivio (1986), some researchers have proposed that the statistical co-occurrence patterns of word-forms across discourses can give rise to a "disembodied" form of conceptual knowledge, and a number of computational studies have shown that, on the basis of such associations among word-forms, it is possible to model a variety of psycholinguistic phenomena, including priming effects, sentence completions, ambiguity resolution, and the extraction of gist from texts (Burgess & Lund, 1997;Landauer & Dumais, 1997;Griffiths et al, 2007;Jones & Mewhort, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Classifications of the social world vary in how gender, race, and social hierarchies are organized (23,24). Classifications of artifacts vary in the very entities there are to be classified, with distinct types of tools, clothing, furniture, and so forth, as well as category boundaries (25). And there is marked linguistic variation in the classification of dimensions of experience, including color, number, time, space, emotions, even senses (26,27).…”
Section: Categories As Cultural Inheritancementioning
confidence: 99%
“…Languages often differ in the contrasts they lexicalize, a phenomenon documented for properties (such as colors and tastes), objects (such as plants, animals, and human-made objects), and relations (such as those captured by spatial terms and many verbs) (for review and discussion, see, e.g., Bowerman & Levinson, 2001;Malt & Majid, 2013;Malt & Wolff, 2010). Given the pervasive diversity, one could counter that the world must present few pre-existing distinctions to the observer, and differences between languages may be arbitrary and unpredictable.…”
Section: Introductionmentioning
confidence: 99%